Modernism and Tradition of Lyrical Abstarction in Bašić’s Poetry - Elbisa Ustamujić (Društvene i Humanističke Studije, 2018)
This paper deals with poetic features of Husein Basic’s poetry in the context of the literary aesthetics of high modernism, to which this versatile author contributed in a considerable extent thus making himself known within the South Slavic inter-literary community. Intercultural and intertextual dialogue with the native Slavic folklore-pagan tradition and its archetypal images are important in the whole of Basić’s work, and can be seen in motifs, style and genre. Bašić belonged to thecircle of “poets of lyrical abstraction”and in his attempt to create a unique voice he formed his poetry by combining the authentic experience of avant-garde, post-realism and existentialism with the values of tradition and cultural roots. In his poetry he takes the theme of war to a universal level and does not overemphasize the Bosniak national identity and dedication to the nation. The linguistic-stylistic analysis of Basić’s poetic images has confirmed the existence of a unique harmony between visual and melodic features in his poetical expression.